Engaging Citizens in Cultural Planning with a Web Map Survey - Nummi, Pilvi; Tzoulas, Tuija (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2015)
This article discusses the use of a web map survey tool for cultural mapping in Nikkilä, in the municipality of Sipoo, Finland. Nikkilä has in place an ongoing cultural planning and development process that involves collaborative planning between the municipal urban planning department and the cultural department. Cultural planning is a culturally sensitive approach in urban development. The main goal in cultural planning is to study ‘sense of place’ and discover what makes the place distinctive. The starting point of the process is to study the experiences and visions of local inhabitants and other public stakeholders regarding the area and its resources. Cultural mapping is a central part of a process that aims to increase the welfare and attractiveness of Nikkilä by utilizing existing cultural resources. This paper describes the participative design process of the web map survey, which was used as a cultural mapping tool to engage citizens to participate in the cultural planning process. Based on the case study, we are convinced that a web map survey is suitable for use as a cultural mapping tool. However, to achieve a good result it is necessary to invest in the design as well as the marketing of the survey. User-centred methods, such as collaborative planning, can be used to engage different user groups in the design of the survey. The earlier that prospective respondents can be involved in the collaborative design of a survey, the better results can be expected, quantitative as well as qualitative.